Volatile aroma compounds in various brewed green teas - Lee, Jeehyun; Chambers, Delores H.; Chambers, Edgar, IV; Adhikari, Koushik; Yoon, Youngmo (My University, 2013)
This study identifies and semi-quantifies aroma volatiles in brewed green tea samples. The objectives of this study were to identify using a gas chromatograph-mass spectrometer (GC-MS) paired with a headspace solid-phase micro-extraction (HS-SPME) the common volatile compounds that may be responsible for aroma/flavor of the brewed liquor of a range of green tea samples from various countries as consumed and to determine if green teas from the same region have similarities in volatile composition when green tea samples are prepared for consumption. Twenty-four green tea samples from eight different countries were brewed as recommended for consumer brewing. The aroma volatiles were extracted by HS-SPME, separated on a gas chromatograph and identified using a mass spectrometer. Thirty-eight compounds were identified and the concentrations were semi-quantified. The concentrations were lower than those reported by other researchers, probably because this research examined headspace volatiles from brewed tea rather than solvent extraction of leaves. No relationship to country of origin was found, which indicates that other factors have a greater influence than country of origin on aroma.
Keywords: Green tea; Aroma; Volatiles; GC-MS; HS-SPME; Gas chromatograph-mass spectrometer; Headspace solid-phase micro-extraction